2000
DOI: 10.1136/gut.46.5.715
|View full text |Cite
|
Sign up to set email alerts
|

Long term effect of alpha interferon in children with chronic hepatitis B

Abstract: Background/aims-The purpose of this study was to better define the long term prognosis of infection and disease in children with chronic hepatitis B treated with interferon (IFN) alpha. Patients-A total of 107 children with chronic hepatitis B who received IFN alpha for three or six months in two clinical trials were followed for a mean period of 69 (17) months. Response to treatment was defined as loss of hepatitis B e antigen (HBeAg) within 12 months after stopping treatment. A control group of 59 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
4
4

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 18 publications
(8 reference statements)
8
78
4
4
Order By: Relevance
“…5,[12][13][14][15] Treatment with lamivudine was not associated with any significant side effects. However, to enable pediatricians to be able to use this agent appropriately, it was important to evaluate treatment over a longer duration, and to evaluate the durability of the treatment response obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[12][13][14][15] Treatment with lamivudine was not associated with any significant side effects. However, to enable pediatricians to be able to use this agent appropriately, it was important to evaluate treatment over a longer duration, and to evaluate the durability of the treatment response obtained.…”
Section: Discussionmentioning
confidence: 99%
“…5,[11][12][13][14][15] Treatment with interferon ␣ has the advantage of a finite duration and does not result in the emergence of HBV mutations associated with resistance. On the other hand, interferon ␣ treatment is expensive and is associated with significant side effects, including transient growth impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Currently none of the HBV treatments fulfill these conditions. With interferon based therapy HBsAg loss occurs in 3%-10% of the patients within one year of start of therapy and increases in sustained responders to 11%-32% [3][4][5][6][7][8][9] . HBsAg loss is rare (< 2% after one year of treatment) in patients treated with nucleos(t)ide analogues, which is about the rate observed in the natural history of the disease [10][11][12][13][14][15][16] .…”
Section: Naïve Patientsmentioning
confidence: 99%
“…Rates of HBsAg loss have been reported in 5-10% of European patients during 1 year of treatment, increasing to 11-25% among sustained responders over a 5-year follow-up period [20,23,25,26]. Long-term follow-up of a group of HBeAg-positive patients who responded to IFN suggested that the remissions induced are of long duration and were followed in most cases by loss of HBsAg and lack of evidence of HBV replication [27].…”
Section: Conventional Interferonmentioning
confidence: 99%